Recent Trends in Spine Topics on the Orthopaedic In-Training Examination. Issue 22 (15th November 2022) - Lambrechts, Mark J.; D'Antonio, Nicholas D.; Heard, Jeremy C.; Kaye, I. David; Vaccaro, Alexander R.; Saxena, Arjun
Abstract : Introduction: The Orthopaedic In-Training Examination (OITE) is an important metric for orthopaedic residents and residency programs to gauge a resident's orthopaedic knowledge. Because the OITE is correlated with the likelihood of passing part I of the American Board of Orthopaedic Surgery, greater emphasis is being placed on the examination. However, a detailed look at the questions most likely to appear on the spine subsection of the OITE has not been done in the past decade. Methods: Digital copies of the OITEs during the years 2017 through 2021 were obtained online through the "ResStudy" program within the American Academy of Orthopaedic Surgeons Online Learning Platform. All spine-related questions were categorized into five different categories including type of spine question (knowledge-based, diagnosis, or evaluation/management), anatomical region, imaging modality provided, subject matter, and referenced journal or textbook. The total number and likelihood of each question type to appear on the OITE were defined as mean and percentage of the total number of spine questions, respectively. Results: A total of 139 spine questions were identified on the OITE during the years 2017 to 2021. The most common type of spine questions were evaluation/management (N = 65) and knowledge-based questions. We identified lumbar (N = 45), cervical (N = 42), thoracolumbar (N = 13), and thoracic (N = 12) as the most commonly tested anatomical regions. Spinal trauma (N = 26), disk disease/disk herniation (N = 16), postoperative complications (N = 15), and scoliosis/sagittal balance (N = 15) were the most commonly tested material. Spine (N = 54) was almost two times more likely to be referenced as the source for the tested material compared with other journals or textbooks. Conclusions: Understanding the spine topics most likely to appear on the OITE may allow orthopaedic residents and residency programs to supplement educational objectives toward the highest yield spine topics and journals.